Using Training as a Tool for Cultivating Communities of Practice around Health Information Systems in Low and Middle Income Countries: A Longitudinal Mixed Method Study. Issue 1 (5th December 2017) - Siribaddana, Pandula; Hewapathirana, Roshan
Abstract: Many attempts at implementing health information systems (HISs) in Low and Middle Income Countries (LMICs) have failed to mature or scale into desirable levels due to various reasons. Among these reasons, not identifying the design reality gap, inability to form support networks and non‐availability of 'hybrids' who can link between health and information systems domains can be highlighted. In organizational contexts, such challenges can be overcome by cultivating communities of practice (CoPs). However, HIS projects in LMIC contexts may not have the opportunity to create an environment similar to an organization to facilitate cultivation of CoPs. This paper argues that HIS projects in LMICs can utilize formal, informal and workplace based online and face‐to‐face training methods along with the networking power of free and open source software (FOSS) communities as a means of cultivating CoPs. In substantiating this argument, the paper utilizes a mixed method longitudinal study design to follow‐up a group of implementers trained in a FOSS HIS in Sri Lanka. The paper presents a practical training model usable in information system implementations in LMIC settings with the added benefit of being able to facilitate cultivation of CoPs. The paper also contributes theoretically by extending the conceptualization of 'cultivating CoPs' beyond organizational contexts.